Case Report on Ruptured Renal Artery Aneurysm - Darouichi, Mohammed; S.Qanadli,; P.E.Constanthin, (Archives of Clinical and Biomedical Research, 2017)
Renal aneurysms are a rare entity with an incidence of 0.09% of the population. They are often asymptomatic and frequently discovered incidentally during abdominal imaging for unrelated causes. Rupture of renal artery aneurysms is a surgical emergency, very often lethal. Swift diagnosis is crucial and is made by ultrasound and abdominal MDCT. We report the case of a renal artery rupture in a 58 year-old man who arrived in the emergency department with left flank pain of sudden onset followed by a hypovolemic shock. MDCT scan showed the rupture of an aneurysm of the left renal artery associated with a retroperitoneal hematoma. It is a life-threatening situation in case of delayed diagnosis. In our case, prompt imaging and diagnosis led to conservative treatment and nephrectomy was avoided.